2017
DOI: 10.3390/genes8110294
|View full text |Cite
|
Sign up to set email alerts
|

How Next-Generation Sequencing Has Aided Our Understanding of the Sequence Composition and Origin of B Chromosomes

Abstract: Accessory, supernumerary, or—most simply—B chromosomes, are found in many eukaryotic karyotypes. These small chromosomes do not follow the usual pattern of segregation, but rather are transmitted in a higher than expected frequency. As increasingly being demonstrated by next-generation sequencing (NGS), their structure comprises fragments of standard (A) chromosomes, although in some plant species, their sequence also includes contributions from organellar genomes. Transcriptomic analyses of various animal and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 80 publications
(79 reference statements)
0
42
0
1
Order By: Relevance
“…Finally, a parallel could be drawn between marker chromosomes generated by chromoanagenesis events and the supernumerary chromosomes, named B chromosomes, found in many eukaryotic karyotypes. It has been established that these supernumerary chromosomes represent multichromosomal mosaics arising in taxa that experienced rapid genome changes [103], like the domestic dog which has one of the most rearranged karyotypes in mammals [104,105].…”
Section: Macro-evolutionary Implications Of Chromoanagenesismentioning
confidence: 99%
“…Finally, a parallel could be drawn between marker chromosomes generated by chromoanagenesis events and the supernumerary chromosomes, named B chromosomes, found in many eukaryotic karyotypes. It has been established that these supernumerary chromosomes represent multichromosomal mosaics arising in taxa that experienced rapid genome changes [103], like the domestic dog which has one of the most rearranged karyotypes in mammals [104,105].…”
Section: Macro-evolutionary Implications Of Chromoanagenesismentioning
confidence: 99%
“…Sequences already on the B collect mutations at a high rate, and most are eventually lost. It has been difficult to produce sequence assemblies of B chromosomes due to their repetitive nature and their high levels of homology with sequences in the A chromosomes [16,17,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Current approaches to identifying B sequence can be categorized into two types: direct and indirect [16]. Direct methods, such as the sequencing of B chromosomes isolated through flow sorting or microdissection, have a high rate of contamination [12,16] and are only possible in a few organisms with large B chromosomes. Indirect methods, such as the comparison of whole genome sequence data between samples with and without a B chromosome, can be performed on any species.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the Bs of several plant and animal species harbour gene-derived sequences. This allowed to trace their origin from duplicated fragments of multiple A chromosomes of their host species (reviewed in (Ruban et al, 2017). Hence, Bs could be considered as a by-product of standard chromosome (As) evolution.…”
Section: Introductionmentioning
confidence: 99%